2007
DOI: 10.1128/jcm.00836-07
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of Reduced Susceptibility to Glycopeptides among Methicillin-Resistant Staphylococcus aureus Isolates from Patients in Ireland and Evaluation of Agar Screening Methods for Detection of Heterogeneously Glycopeptide-Intermediate S. aureus

Abstract: Methicillin-resistant Staphylococcus aureus (MRSA) isolates (n ‫؍‬3

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
37
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(37 citation statements)
references
References 22 publications
0
37
0
Order By: Relevance
“…Various screening methods for strains with reduced vancomycin susceptibilities have been described previously (33,34); however, confirmation of the resistance phenotypes of screening-positive isolates by population analyses is recommended (8,18). This study revealed a slight increase in strains with reduced vancomycin susceptibilities over time at a university hospital in northeast Thailand.…”
Section: ϫ6mentioning
confidence: 83%
“…Various screening methods for strains with reduced vancomycin susceptibilities have been described previously (33,34); however, confirmation of the resistance phenotypes of screening-positive isolates by population analyses is recommended (8,18). This study revealed a slight increase in strains with reduced vancomycin susceptibilities over time at a university hospital in northeast Thailand.…”
Section: ϫ6mentioning
confidence: 83%
“…After the first reports of VISA and hVISA from Japan, it did not take long for this resistance phenotype to be recognized around the world. Strains of S. aureus (predominately MRSA) demonstrating the hVISA or VISA phenotype have now been reported for many countries including the United States, Japan, Australia, France, Scotland, Brazil, South Korea, Hong Kong, South Africa, Thailand, Israel, and others (22,67,69,77,79,82,94,158,167,194,195,206,258,284,300,326,327,331,352,354,366,373). A retrospective analysis of stored isolates detected previously unrecognized hVISA/VISA strains at least back to 1987 in the United States and back to a similar period in France, Spain, and Germany (11,22,39,276,288); however, there has been some concern about the potential loss of resistance during prolonged storage, which could impact results of such retrospective analyses.…”
Section: Global Epidemiology and Associated Features Of Hvisa And Visamentioning
confidence: 99%
“…The use of BHIA with 3 g vancomycin per ml inoculated with 10 l of a 0.5-McFarland-standard suspension had a high false-positive rate reported by one study (165). Fitzgibbon et al assessed a range of screening media for the detection of hVISA (MHA with 5 g teicoplanin per ml and BHIA with 5 g teicoplanin per ml), all inoculated with 10 l of a 0.5-McFarland-standard suspension, a 2-McFarland-standard suspension, and a BHIB stationary-phase culture (82). The hVISA-positive isolates were confirmed by PAP but included isolates that were positive for hetero-teicoplanin resistance but negative for hVISA by PAP.…”
Section: Hvisamentioning
confidence: 99%
“…Agar screening test was performed as described previously (Fitzgibbon et al, 2007). All isolates were screened on brain heart infusion (BHI) agar supplemented with 4 g/ml vancomycin (BHIV4) and 6 g/ml vancomycin (BHIV6) by using 10 l of bacterial suspensions of a 0.5 McFarland suspension.…”
Section: Vancomycin Agar Screening Testmentioning
confidence: 99%
“…hVISA was screened by MET described by (Fitzgibbon et al, 2007). Namely, 200 l of 2.0 MaFarland suspensions was pipetted onto a BHI agar plate.…”
Section: The Macro E Test (Met)mentioning
confidence: 99%